Unveiling the potentials of wine tourism: the way ahead for Limassol - Liasidou, Sotiroula (My University, 2018)
Purpose: The paper aims to bring together Limassol’s rich wine culture with the contemporary facet of its developing infrastructure and superstructure as a means through which to promote this city as a tourist destination. Additionally, to identify how Limassol can be experienced in relation to the wine culture based on the experience economy model of Pine and Gilmore (1999) Limassol is a seaside city in Cyprus that has developed extensively over the past few years, with a new infrastructure and superstructure that attracts foreign investments. Additionally, the city has a rich wine history with a particular emphasis on “Commanadaria wine” that originates in the twelfth century and is directly linked with the Richard the Lionheart king of England and the Third Crusade. Design/methodology/approach: The methodology used was qualitative research, and in particular semi-structured interviews with professionals involved in the tourism industry in Limassol. A particular method was used to understand the ways in which wine history and culture permeate and influence the contemporary way of life in Limassol as a tourist destination. Findings: The main results of this study suggest that Limassol has the potential to become an important destination that fulfils the requirements of the experience economy as put forth by Pine and Gilmore (1999). However, the main hindrance is the lack of a constructive tourism policy exclusive on wine tourism that will give a stronger identity to Limassol. Originality/value: This research is original in nature because it considers a novice geographical area, Limassol, in the academic field. Thus, it is set as the cornerstone for further investigation on wine and tourism in Limassol. The managerial implications of the study are related to the engagement in wine culture, and in providing a unique identity to the city that can be promoted internationally.
Keywords: Cyprus; Experience economy; Interviews; Limassol; Wine tourism